2011
DOI: 10.3892/ol.2011.340
|View full text |Cite
|
Sign up to set email alerts
|

Tissue factor pathway inhibitor-2 inhibits the growth and invasion of hepatocellular carcinoma cells and is inactivated in human hepatocellular carcinoma

Abstract: Abstract. Human tissue factor pathway inhibitor-2 (TFPI-2) is an extracellular matrix-associated Kunitz-type serine proteinase inhibitor that inhibits the plasmin-and trypsinmediated activation of matrix metalloproteinases and inhibits tumor progression, invasion and metastasis. Previous studies have shown that TFPI-2 is downregulated in the progression of various tumors. The purpose of this study was to investigate the expression and function of TFPI-2 in hepatocellular carcinoma (HCC). In situ hybridization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Also, a role for DKK1 as a tumor suppressor by Wnt-signaling inhibition was documented (53). Tissue factor pathway inhibitor-2 (TFPI-2) is a matrix-associated serine protease inhibitor, which has been previously described as a tumor suppressor gene in several types of cancer (54, 55). Our results therefore support the notion that FLASH represses the expression of numerous genes that support the epithelial phenotype and therefore is a critical determinant of the mesenchymal phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a role for DKK1 as a tumor suppressor by Wnt-signaling inhibition was documented (53). Tissue factor pathway inhibitor-2 (TFPI-2) is a matrix-associated serine protease inhibitor, which has been previously described as a tumor suppressor gene in several types of cancer (54, 55). Our results therefore support the notion that FLASH represses the expression of numerous genes that support the epithelial phenotype and therefore is a critical determinant of the mesenchymal phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported that TFPI-2 is produced and secreted into the extracellular medium where it acts as a serine proteinase inhibitor 7 , 9 , 13 . To determine the secretion levels of TFPI-2, we employed ELISA experiments.…”
Section: Resultsmentioning
confidence: 99%
“…TFPI-2 has been recently recognized as a tumor suppressor, playing a suppressive role in tumor cell proliferation, apoptosis, invasion and angiogenesis 7 9 . Down-regulation of TFPI-2 expression, due to hypermethylation of its promoter, was seen in some highly aggressive tumors such as glioma, non-small cell lung cancer and breast cancers 8 , 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy and apoptosis synergistically affect each other [7] . Hepatocellular carcinoma (HCC) is a common primary tumor [9,10] . With the development of diagnostic imaging and advanced treatments in recent years, clinicians have adopted radical treatment strategies, such as surgical resection, liver transplantation, and radiofrequency ablation therapy.…”
Section: Original Articlementioning
confidence: 99%